Prejudicial To Public Order: Legal Issues On Banning Book In Malaysia - Mohd Zamre Mohd Zahir; Ramalinggam Rajamanickam; Nur Khalidah Dahlan; Mohd Safri Mohammed Na’aim; Hasnizam Hashim; Nabeel Mahdi Althabhawi (Soran University (SU), 2024)
Non-Indexed Publication